Punishing Protesters on the “Other Side”: Partisan Bias in Public Support for Repressive and Punitive Responses to Protest Violence - Jason R. Silver; Luzi Shi (Socius, 2023)
The authors investigated public support for government repression of protests (police repression, legal repression, and punishment of protesters) following incidents of violence and harm. Using two factorial vignette experiments embedded in a national Qualtrics survey ( n  = 1,229), the authors examined whether partisan bias (i.e., polarized responses to actions by ideological opponents or allies) characterized public preferences for repressive government responses to intentional violence (i.e., rock throwing) or incidental harm (i.e., coronavirus disease 2019 transmission) occurring at protests. The authors also examined whether violence or harm severity, or violence against or harm to police, influenced the degree of partisan bias in public responses. The results indicated partisan bias in support of police repression and punishment preferences and, to a lesser extent, legal repression. Members of the public preferred more repressive responses to political opponents and less repressive responses to political allies. Partisan bias in preferences for punishment was also heightened when a police officer was the target of intentional violence.